The Effect of Special Exercises in Soccer Skill Tests for Young Players - Jasim, mohammedjasim; Hassan, Uday (Journal of Physical Education, 2024)
The aim of the research is to develop the skill aspect of soccer side among the young players age of (15) years old, because these skills are the basis for the player at the beginning of a way towards developing the rest of the skills. The researcher used the experimental method. The research sample consisted of young players, Al-Kahraba Club, with (10) players (the control group). The subjects were (10) young soccer players from The AL-Zwraa Club. A set of special exercises were designed and the program was applied for developing the basic skills (passing, trapping, dribbling and scoring) for (8) weeks followed by tests. The data was collected and treated using proper statistical operations to conclude a weakness in the skill side of young soccer players and that the proposed program of special exercises have an effective role on developing these skills in young soccer players. Finally the results showed that were working with their coach.